Archiwum w biografii. Biograf/ka w archiwum - Lucyna Marzec, Lucyna Marzec (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
The article discusses the role of the archive in biographical narrations and the relationship between the biographer and the archive in research practice. It discusses author’s metacomment in contemporary biographies, articles on archive research, memoirs and novels (by A. Y. Kaplan, Ryszard Matuszewski, J. P. Sartre, Monika Rudaś-Grodzka, Joanna Krakowska, Joanna Kuciel-Frydryszak, Olof Lagercrantz and others). A key role in understanding their texts is played by a philological imagination and memory as elements of creating a biography, daily work in the archive and placing the biographer and the archive both in the process of creating knowledge and in the narrative figures.